PENGARUH PELAYANAN PAJAK, PENGETAHUAN WAJIB PAJAK, KESADARAN WAJIB PAJAK, DAN SANKSI PAJAK TERHADAP PENERIMAAN PAJAK KENDARAAN BERMOTOR DI SAMSAT KAB DAIRI - Sigiro, Windi; Sitanggang, Abdonsius; Pangaribuan, Jonner (Jurnal Ilmiah Akuntansi (JIMAT), 2024)
This study aims to determine the factors that affect the motor vehicle tax revenue target at Samsat Kab Dairi. The population used in this study used all taxpayers of Samsat Kab Dairi, with a research sample of 100 taxpayers known by using the slovin technique. The data collection technique was carried out by questionnaire method and processed using SPSS 25 software. The data analysis techniques used in this research are descriptive statistics, data validity test, multiple linea r regression. Based on partial tests that the factors that affect motor vehicle tax revenue are tax services, tax knowledge, tax awareness, tax sanctions have a positive effect, meaning that the higher the tax service, tax knowledge, tax awareness, tax sanctions, the tax revenue of motorized vehicles increases at Samsat Kab Dairi.